Konjac glucomannan microcarriers: an application in the treatment of pulmonary tuberculosis - Guerreiro, Filipa Raquel Horta (2022)
Tuberculosis remains one of the leading causes of death worldwide.1 The conventional therapy of this infection is based on the intake of a combination of several antitubercular drugs for a period that could reach 2 years.2 The prolonged treatment of tuberculosis has limited the therapeutic success, as it fosters the non-compliance of the patient and, consequently, the emergence of drug resistance.3 Thus, the development of new approaches to treat tuberculosis is demanded to address the limitations of the current treatment. Considering that 80% of tuberculosis cases are pulmonary, the direct delivery of antitubercular drugs to the lungs has been explored as therapeutic alternative in recent years. This approach is thought to potentially allow to decrease the dose and frequency of drug administration, while reducing the treatment duration and the systemic side effects associated to the conventional therapy of tuberculosis.4 Its success requires the engineering of suitable carriers, which must reach the alveolar region, where the macrophages infected with Mycobacterium tuberculosis are located, and undergo phagocytosis by these cells.5 On the other side, specific receptors existing on macrophage surface may be used as drug targets in a strategy where drug carriers may, again, play a relevant role. At this moment, there are few excipients approved for pulmonary delivery applications, which hinders the development of drug carriers.6 The work entailing this PhD thesis proposes the development of inhalable microparticles based on konjac glucomannan (KGM), which are targeted to the alveolar macrophages. KGM is a polysaccharide composed by mannose and glucose units.7 The rational beyond the proposed strategy relies on the fact that the presence of mannose on KGM microparticles may mediate a preferential recognition by the mannose receptors present on the macrophage surface and potentiate their phagocytosis via these receptors.8 Inhalable microparticles were produced in the form of dry powders by a technique of spray-drying. In order to have KGM with the suitable properties for microparticle production using this technique, the polymer was initially submitted to an acid hydrolysis, which was demonstrated to not affect its physicochemical characteristics (composition and glucose/mannose ratio) and permitted a successful processing by spray-drying to produce microparticles. Isoniazid (INH) and rifabutin (RFB) are first-line antitubercular drugs and were associated to KGM microparticles as model drugs. Various formulations of drug-loaded KGM microparticles were produced (KGM/INH/RFB = 10/1/0.5, 10/1/1, 10/2/0.5, w/w) and subsequently characterised. Drug association efficiency varied within 66% and 91%, and the release of the drugs in conditions resembling the alveolar environment showed slower release of RFB compared with INH, but complete release of both drugs within 24 h. Regarding to the aerodynamic characteristics, which are of utmost importance in lung delivery strategies, KGM microparticles exhibited aerodynamic diameters around 3 μm, regardless of the drug amounts, which evidences suitability to reach the alveolar zone. Additionally, the spherical shape and the geometric size of approximately 2 μm displayed by KGM microparticles has proven adequate for macrophage internalisation, as shown in an in vitro assay. In fact, approximately 100% of macrophage-like THP-1 cells in culture demonstrated to phagocytose the microparticles. Despite the uptake was demonstrated, macrophage activation upon exposure to microparticles was not observed. As mentioned before, a relevant limitation of the pulmonary drug delivery field relies on the shortness of excipients approved for inhalation. One of the main reasons for that is the unknown fate of materials after deposition in the lungs. In this work, the swelling of (unloaded) KGM microparticles was observed to occur (40% - 50%) upon liquid contact, but size reduction (> 62% in 90 min) in presence of β-mannosidase, an enzyme present in the lung, was further demonstrated, indicating potential biodegradability upon inhalation. The preservation of antibacterial effect of the used drugs after spray-drying was demonstrated using Mycobacterium bovis, evidencing an absence of effect of the process of microencapsulation. In fact, the minimum inhibitory concentration (MIC) remained similar to that determined for the free drugs. However, a preliminary study indicated that the amount of drug corresponding to MIC was not enough to kill the bacteria after infection of the macrophages (macrophage-like THP-1 cells) with M. bovis. The number of bacteria surviving in macrophages only decreased on the ninth day of infection. Moreover, the continued exposure of bacteria to KGM microparticles for 7 days suggested the development of a certain degree of drug resistance by M. bovis. Finally, to better support the proposal of using KGM in lung delivery applications, the safety of KGM microparticles was evaluated in vitro and in vivo. With regards to the in vitro tests, these focused on the evaluation of toxicological profile in respiratory cells (alveolar epithelium and macrophages). Despite a wide range of concentrations was assessed to have a more comprehensive knowledge on the effect of the material and the developed drug carrier, at the concentrations expected to be realistic in approaches of lung delivery (up to 125 μg/mL) drug-loaded KGM microparticles did not show overt cell toxicity. An in vivo assay was also performed which focused on evaluating the toxicity of the material itself, as it is not approved for lung delivery applications. Mice receiving daily administration of unloaded KGM microparticles by inhalation for a period of two weeks have shown no signs of systemic or lung inflammatory response, which is in line with the results of macrophage activation obtained in vitro. Moreover, histological examination of the lung revealed no differences upon inhalation, comparing with control naïve mice, although some unexpected observations transversal to all groups require clarification. The results further demonstrated the development of eosinophilia, which is typically associated to allergic reactions. Nevertheless, no alterations were observed in serum IgE upon inhalation, which opposes to the eosinophilic effect. Overall, despite some positive indications, regulations on safety evaluation include a vast number of parameters to assess and further studies are required to deepen the assessment and support the safety of KGM for lung delivery applications. Considering the whole set of data generated throughout the work, encouraging indications were given on the potential of KGM to be used as a pharmaceutical excipient in the formulation of inhalable antitubercular drug carriers for pulmonary tuberculosis treatment and, potentially, in other applications benefiting from macrophage targeting.